Nutritional retention and sensory properties of novel tropical vegetable juice formulations prepared via non-thermal processing - Abu Bakar, Ibrahim (ijcsrr.org, 2026)
The development of functional beverages derived from tropical vegetables offers growing potential within the global health-focused food sector. This study formulated and evaluated three non-thermally processed Tropical Vegetable Juice Formulations (TVJF) using Ipomoea aquatica (kangkung) as the primary raw material. The objectives were to compare nutrient retention between juice and raw leaves, assess consumer sensory acceptance across different formulations, and evaluate commercialisation potential. Proximate and mineral analyses were conducted on TVJF-K and compared with raw vegetable samples using standard AOAC methods, while sensory evaluation of three formulations (TVJF-1, TVJF-2, and TVJF-3) employed a 5-point hedonic scale assessing colour, aroma, texture/stability, flavour, and overall acceptance among 30 untrained panelists. Results indicated that the juice retained approximately 80–95% of key minerals, particularly calcium, magnesium, iron, and copper, demonstrating effective preservation through non-thermal cold extraction. Sensory analysis revealed no significant differences (p > 0.05) in colour, aroma, flavour, or overall acceptance among formulations, although texture/stability differed significantly (p = 0.02). All formulations achieved mean scores above 3.0, indicating favourable consumer acceptance. These findings demonstrate that simple non-thermal processing can maintain both nutritional integrity and sensory quality in tropical vegetable juices, highlighting strong potential for industrial application, product diversification, and expansion within the regional functional beverage market.